Review of the role and potential clinical value of m6A methylation modifications in the biological process of osteosarcoma - Zhou, Huaqiang; Shu, Rongbing; Wu, Jianming; Zhou, Jiangjun; Yu, Zhuanyi; Cheng, Qiuxin; Peng, Zhihao; Zhao, Min (Frontiers in Genetics, 2025)
Osteosarcoma (OS), an aggressive bone tumor, is a substantial threat to the quality of life and survival of affected individuals. Despite recent improvements in OS therapies, the considerable variability and chemotherapy resistance of this cancer necessitate continuous research to discover new treatment targets and biomarkers. Recent epigenetic advances highlight the crucial role of N6-methyladenosine (m6A) methylation in cancer. In OS, m6A methylation has been demonstrated to be a pivotal component in the pathogenesis. This review introduces new findings regarding the association between m6A methylation regulators and OS, and summarizes the potential clinical applications of OS and m6A methylation regulators, including the role of m6A methylation in OS proliferation, growth, apoptosis, and cell migration, invasion, and metastasis; relationship between m6A methylation and OS chemotherapy resistance; and relationship between m6A methylation and OS prognosis. Our review had certain limitations. The interaction between m6A methylation regulators and other oncogenic factors, such as lncRNAs and ncRNAs, is not fully understood. We hope that these potential methods will be translated into clinical applications and effective treatment.